Mesenchymal stem cells for peripheral nerve injury and regeneration: a bibliometric and visualization study - Aisaiti, Aikebaierjiang; Aierxiding, Shalayiding; Shoukeer, Kutiluke; Muheremu, Aikeremujiang (Frontiers in Neurology, 2024)
Objective To use bibliometric methods to analyze the research hotspots and future development trends regarding the application of mesenchymal stem cells in peripheral nerve injury and regeneration. Methods Articles published from January 1, 2013, to December 31, 2023, were meticulously screened using the MeSH terms: TS = (“Mesenchymal stem cells” AND “Peripheral nerve injury”) OR TS = (“Mesenchymal stem cells” AND “Peripheral nerve regeneration”) within the Web of Science database. The compiled data was then subjected to in-depth analysis with the aid of VOSviewer and Cite Space software, which facilitated the identification of the most productive countries, organizations, authors, and the predominant keywords prevalent within this research domain. Results An extensive search of the Web of Science database yielded 350 relevant publications. These scholarly works were authored by 2,049 collaborative researchers representing 41 countries and affiliated with 585 diverse academic and research institutions. The findings from this research were disseminated across 167 various journals, and the publications collectively cited 21,064 references from 3,339 distinct journals. Conclusion Over the past decade, there has been a consistent upward trajectory in the number of publications and citations pertaining to the use of mesenchymal stem cells in the realm of peripheral nerve injury and regeneration. The domain of stem cell therapy for nerve injury has emerged as a prime focus of research, with mesenchymal stem cell therapy taking center stage due to its considerable promise in the treatment of nerve injuries. This therapeutic approach holds the potential to significantly enhance treatment options and rehabilitation prospects for patients suffering from such injuries.